Undergraduates' writing in discussion text - Chai, Ai Sze (University Malaysia Sarawak, (UNIMAS), 2009)
This case study examined the ability of undergraduates to handle the discussion text type that required by in the examination of the generic course PBI 1032 Academic Reading and Writing (ARW) in second term in year 2007/08 at University Malaysia Sarawak, with a specific focus on the structure and language features significant to the text-type. A total of 101 sample discussion texts obtained from undergraduates from different programmes and faculties at Universiti Malaysia Sarawak. The results showed that the undergraduates only meet the qualities of the discussion text partially. Most of the undergraduates able to construct acceptable statement of issue, leading with Argument with relevant and adequate details and evidences were provided to explain the points. Text analysis of the sample discussion texts using the frameworks of Feez (1998) showed that the Argument Against and Assessment of the discussion text were the most difficult in terms of the text structure. There are two common mistakes that can be detected in the sample texts namely: (1) irrelevant points and (2) relevant content with the targeted issue but many lack the defining characteristics of the text type in its structure and style, particularly in assessment of the discussion text. The analysis of linguistic choices indicated most of the undergraduates were more competent and familiar with the conditional clauses, conjunction and modal verbs in order fulfill the purpose of the text type. There are 42 types of conjunctions that used to link the ideas in the sentences but the undergraduates had showed difficulties in using certain modal verbs to show the necessity in writing.